K-State Turfgrass Research 2009 - Kansas State University. Agricultural Experiment Station and Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2009)
Turfgrass Research 2009 contains results of projects conducted by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day on August 6, 2009, at the John C. Pair Horticultural Center in Wichita, KS. Articles in this Report of Progress summarize research projects that were completed recently or will be completed in the next year or two. Specifically, this year's report presents summaries of research on environmental stresses and the environment, disease control, and cultivar evaluations.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); xxx; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1015; Turfgrass; Stress management; Disease control; Creeping Bentgrass; Zoysiagrass; Bermudagrass